2005
DOI: 10.1007/s00595-004-2915-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Fibrous Histiocytoma of the Ascending Colon: Report of a Case

Abstract: We report a rare case of primary malignant fibrous histiocytoma (MFH) of the ascending colon. A 66-year-old man presented to our hospital with epigastralgia, and abdominal ultrasonography and computed tomography showed a large soft-tissue mass in the ascending colon. Barium enema and endoscopic examination showed a huge tumor in the ascending colon. At laparotomy, we found a tumor in the ascending colon and performed a right hemicolectomy with en bloc lymph node dissection. The resected specimen contained a tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Most tumors are large, ranging from 2 cm to 19 cm in diameter (median diameter, 7 cm), and the tumor in our patient is probably one of the smallest tumor observed. The distribution differs from more common types of colorectal cancer [22] . The tumor locations include nine in the right-sided colon, seven in the transverse and descending colon, three in the sigmoid colon, and four in the anorectum.…”
Section: Discussionmentioning
confidence: 80%
“…Most tumors are large, ranging from 2 cm to 19 cm in diameter (median diameter, 7 cm), and the tumor in our patient is probably one of the smallest tumor observed. The distribution differs from more common types of colorectal cancer [22] . The tumor locations include nine in the right-sided colon, seven in the transverse and descending colon, three in the sigmoid colon, and four in the anorectum.…”
Section: Discussionmentioning
confidence: 80%
“…As regards the histological and immunohistochemical staining results, MFH is composed of histiocytic as well as fibrous elements, often arranged in a storiform pattern and accompanied by pleomorphic giant cells, xanthoma cells and inflammatory cells (7). It was reported that MFH frequently expresses vimentin, actin, CD68, α 1-antitrypsin and α 1-antichymotrypsin, and often laminin mRNA (10).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant fibrous histiocytoma (MFH) was first described [3,5] . The peak incidence of extraintestinal MFH occurs in the sixth and seventh decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…Primar y MFH of the intestine is ver y rare. Not more than 40 cases have been reported in international literatures [1][2][3][4] . We reviewed the total 37 cases of intestinal MFH, including ours, and summarized the findings as follow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation